(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main purpose of this study is to examine the underlying factors that influences consumer buying behaviour. This study seeks to efficiently evaluate the possible factors that are responsible for how much or how little a consumer buys. The technique applied throughout the research is entirely qualitative. The limitation of this study is that no concrete quantitative data was included to statistically backup whatever decision was arrived at. At the end of the study, it was concluded that there are four most important factors that affect consumers buying behaviour; personal factors economic factors psychological factors and social factors. These factors in their entirety influences the buying decision of any consumer at any point in time.